Os labirintos da memória em Orfãos do Eldorado de Milton Hatoum - Lemos, Vivian de Assis [UNESP] (2012)
This article aims to analyze aspects of Orfãos do Eldorado (2008), by Milton Hatoum, to elucidate the plot construction by the use of memory, which articulates three narrative perspectives: the mythic, the social-historic and the mythic-social-personal. This process presents as a result a textual configuration marked by a contemporary diction, by the creative work and by a certain lyricism that allows us to say, as Tania Pellegrini and Alfredo Bosi, that there is a ‘revisitated’ regionalism in this author work.